Pengaruh Citra Perusahaan dan Kualitas Layanan M-Banking Terhadap Kepuasan Nasabah Bank BRI (Studi Pengguna BRImo kota Medan) - Kristina H. Lumbanraja, Berkat; Mardhiyah, Ainun (Teewan Journal Solutions, 2025)
Marketing is one of the main activities carried out by entrepreneurs in their efforts to maintain the survival of their business and to develop the company and to obtain maximum profit or profit. Bank BRI in its marketing certainly utilizes technological developments to launch mobile banking (BRImo) to get customer satisfaction and improve the company's image and service quality to match customer desires and expectations. The company's image and service quality can be in the form of satisfying service, working well and quickly, the BRImo application is easy to access and use, and BRI banks are skilled in serving the needs of customers. The purpose of this study was to analyze how the influence of corporate image and M-Banking service quality on the level of customer satisfaction of BRI bank BRImo users in Medan city. The influence between corporate image and M-Banking service quality will be analyzed partially and simultaneously on the level of customer satisfaction. The research method is quantitative with an associative approach. Sampling was done through purposive sampling technique using 100 respondents as samples. The results of this study indicate that the corporate image variable (X1), and the quality of M-Banking services (X2) have a simultaneous (joint) effect on the customer satisfaction level variable (Y) with an Adjusted R Square value of 0.806, it can be concluded that 80.6% of the customer satisfaction level variable can be explained by the corporate image and M-Banking service quality. In conclusion, Bank BRI needs to maintain and improve its corporate image and continue to improve the quality of M-Banking services to ensure continuous customer satisfaction.